[OP.4A.08] A RANDOMIZED DOUBLE-BLIND PLACEBO CONTROLLED CROSSOVER STUDY TO COMPARE QGC001, A BRAIN AMINOPEPTIDASE A INHIBITOR, WITH PLACEBO IN PATIENTS WITH GRADE I/ II ESSENTIAL HYPERTENSION. (September 2017) - Azizi, M.; Courand, P.; Denolle, T.; Zhygalina, V.; Delsart, P.; Amar, L.; Lantelme, P.; Deplanque, D.; Mounier-Vehier, C.; Balavoine, F.; Madonna, O.; Llorens-Cortes, C.
Abstract : Objective: To assess the hemodynamic and hormonal effects, the safety and tolerability of QGC001, a brain aminopeptidase A inhibitor, in hypertensive patients compared to placebo. Design and method: After 2-week period of discontinuation of current antihypertensive therapy and a 2-week placebo run-in period, patients with grade I to II hypertension confirmed by daytime ABPM (above or equal to 135 or 85 mmHg) were randomly assigned to two-periods of 4-week oral QGC001 (250 mg b.i.d. for 1 week uptitrated to 500 mg b.i.d. for 3 weeks) or placebo in crossover study. Safety biochemical parameters and plasma hormone concentrations (active renin, aldosterone, cortisol, copeptin and apelin) were measured at 09:00 (trough) before and after 4-week of QGC001 or placebo administration. The primary endpoint was the difference in the change from baseline in daytime ambulatory SBP (dASBP) after 4-week of QGC001 or placebo. Results: 50 patients were screened, 40 entered the run-in period, 34 were randomized (intention-to-treat population) and 30 completed the study (56.6 ± 9.1 years; 73.5% men; 88.2% white). dASBP, nighttime ambulatory SBP (nASBP), and office SBP (OSBP) results (mmHg) are shown in table 1. Figure. No caption available. There was no significant effect of QGC001 on any of the hormonal parameters. 14 patients (42.4%) had a total of 16 reversible adverse events (AE) of mild intensity during the study. A single episode of reversible macular rash with facial oedema occurred during the QGC001 period. There was no change in safety biochemical parameters. Conclusions: Four-week administration of 1000 mg/d QGC001 decreased dASBP by 2.7 mmHg and OSBP by 4.7 mmHg compared to placebo. QGC001 administration was safe, with the exception of occurrence of one episode of macular rash.